Prenatal diagnosis of low-level mosaic trisomy 20 by amniocentesis in a pregnancy with a favorable outcome - Chih-Ping Chen; Yu-Ling Kuo; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Li-Feng Chen; Wayseen Wang (Elsevier, 2020)
Objective: We present prenatal diagnosis of low-level mosaic trisomy 20 by amniocentesis in a pregnancy with a favorable outcome. Case report: A 35-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XX,+20[8]/46,XX[23]. The parental karyotypes were normal, and prenatal ultrasound findings were unremarkable. Repeat amniocentesis performed at 20 weeks of gestation revealed a karyotype of 47,XX,+20[2]/46,XX[19]. Simultaneous molecular cytogenetic tests using uncultured amniocytes revealed no genomic imbalance in array comparative genomic hybridization (aCGH) analysis and a mosaic level of 14.3% (15/105 cells) in interphase fluorescence in situ hybridization (FISH) analysis. Polymorphic DNA marker analysis using the DNAs extracted from uncultured amniocytes and parental bloods excluded uniparental disomy 20. At 39 weeks of gestation, a phenotypically normal 3580-g female baby was delivered without any structural abnormality. The neonate was doing well at age two years during postnatal follow-ups. Her psychomotor development was normal. Interphase FISH analysis of urinary cells revealed no trisomy 20 signals in 45/45 urinary cells. The peripheral blood had a karyotype of 46,XX in 40/40 lymphocytes. Conclusion: Fetuses with low-level mosaic trisomy 20 at amniocentesis can have a favorable outcome. Molecular cytogenetic analysis on uncultured amniocytes is useful for confirmatory diagnosis of the mosaic level in case of mosaic trisomy 20 at amniocentesis with different mosaic levels at different amniocenteses. Keywords: Amniocentesis, Mosaicism, Mosaic trisomy 20, Trisomy 20